A Homoleptic Alkynyl‐Ligated [Au13Ag16L24]3− Cluster as a Catalytically Active Eight‐Electron Superatom. Issue 2 (20th November 2020) - Qin, Zhaoxian; Sharma, Sachil; Wan, Chong‐qing; Malola, Sami; Xu, Wen‐wu; Häkkinen, Hannu; Li, Gao
Abstract: A new alkynylated cluster [Au13 Ag16 (C10 H6 NO)24 ] 3− is prepared by a NaBH4 mediated reduction method. The AuAg clusters are confirmed by sophisticated characterization techniques. It has a unique "Aucenter @Ag12 @Au12 Ag4 " metal framework which is protected by 24 atypical alkyne ligands L (L=C10 H6 NO). The ligands construct a unique type of motif L‐(Ag)‐Au‐(Ag)‐L at the cluster interface, where the alkyne (C≡C) group of each L was linked by sharing an Au atom through the σ bonds and each C≡C group was discretely connected to a chemically different Ag atom (Agicosahedral /Agcap ) through π bonds. The electronic and optical properties of [Au13 Ag16 L24 ] 3− were studied. DFT characterized the cluster as a clear 8‐electron superatom, and peaks in the optical absorption spectrum were interpreted in terms of the P and D superatom states. The supported Au13 Ag16 L24 /CeO2 catalyst exhibited high catalytic activity and selectivity towards the A 3 ‐coupling reaction involving benzaldehyde, diethylamine, and phenylacetylene. Abstract : An alkynylated cluster [Au13 Ag16 (C10 H6 NO)24 ] 3− is prepared by NaBH4 mediated reduction method. DFT characterized the cluster as a clear 8‐electron superatom. The supported Au13 Ag16 L24 /CeO2 catalyst exhibited high catalytic activity and selectivity towards the A 3 ‐coupling reaction involving benzaldehyde, diethylamine, and phenylacetylene